2021
DOI: 10.3390/ijms22189929
|View full text |Cite
|
Sign up to set email alerts
|

Uridine Treatment of the First Known Case of SLC25A36 Deficiency

Abstract: SLC25A36 is a pyrimidine nucleotide carrier playing an important role in maintaining mitochondrial biogenesis. Deficiencies in SLC25A36 in mouse embryonic stem cells have been associated with mtDNA depletion as well as mitochondrial dysfunction. In human beings, diseases triggered by SLC25A36 mutations have not been described yet. We report the first known case of SLC25A36 deficiency in a 12-year-old patient with hypothyroidism, hyperinsulinism, hyperammonemia, chronical obstipation, short stature, along with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(24 citation statements)
references
References 35 publications
4
18
2
Order By: Relevance
“…We demonstrate that HI/HA syndrome, known to be caused by gain of function mutations in GLUD1 , may also be caused by a biallelic mutation in SLC25A36 , confirming two recent independent publications 8,9 . SLC25A36 encodes a member of the nuclear‐encoded solute carrier 25 (SLC25) family, also known as the mitochondrial carrier family (MCF).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We demonstrate that HI/HA syndrome, known to be caused by gain of function mutations in GLUD1 , may also be caused by a biallelic mutation in SLC25A36 , confirming two recent independent publications 8,9 . SLC25A36 encodes a member of the nuclear‐encoded solute carrier 25 (SLC25) family, also known as the mitochondrial carrier family (MCF).…”
Section: Discussionsupporting
confidence: 87%
“…Through linkage analysis, whole‐exome sequencing (WES), and segregation analysis, a homozygous SLC25A36 mutation was identified at the splicing canonical donor site between exons 3–4, resulting in skipping of exon 3. Our results are in line with the two recent independent studies, demonstrating SLC25A36 mutations causing HI/HA syndrome 8,9 . We clearly delineate the disease phenotype and summarize the seven cases known to date.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…The second approach using the EPRA method provides a quantitative measure of the mutation effect on the transport capacity and has been employed to assess the effects of many disease-causing mutations in other MCs. [128][129][130][131][132][133][134][135][136][137][138][139] The recombinantly expressed SLC25A26 mutants p.Ala102Val, p.Pro199Leu and the truncated variant displayed virtually abolished transport activity, whereas p.Val148Gly was about 15% active compared with the wild-type protein. 127 The results of the first and second approaches are therefore fairly well in agreement.…”
Section: Disorders Associated With Mitochondrial Sam Transportmentioning
confidence: 99%
“…It was also shown that the latter variant was not targeted to mitochondria. The second approach using the EPRA method provides a quantitative measure of the mutation effect on the transport capacity and has been employed to assess the effects of many disease‐causing mutations in other MCs 128–139 . The recombinantly expressed SLC25A26 mutants p.Ala102Val, p.Pro199Leu and the truncated variant displayed virtually abolished transport activity, whereas p.Val148Gly was about 15% active compared with the wild‐type protein 127 .…”
Section: Diseases Associated With Mitochondrial Sam Transport and Met...mentioning
confidence: 99%